Design of a micro pole-climbing robot. (17th June 2019) - Qiaoling, Du; Yan, Li; Sinan, Liu
Pole-climbing robots are increasingly needed to carry out high-risk tasks for human beings. A micro pole-climbing robot is designed in this article. A strategy of climbing pole is proposed, which has high precision in each stride. To enable the robot to sample the angle relative to the ground in real time, micro electro mechanical systems (MEMS) three-axis accelerometers are equipped on micro pole-climbing robot. Accelerometer measurements provide an absolute reference for the pitch-and-roll components of the estimated orientation, which are used as feedback input signal of proportional–integral–derivative algorithm. A supporting structure is installed at the joint of each gripper to assist the robot to clamp a pole. The support structure improves the load capacity of the robot. The maximum load of micro pole-climbing robot is 3.5 times its own weight. The climbing pole strategy includes the following sections: a Denavit–Hartenberg model is established and the inverse kinematic solution is analyzed; the flip locomotion is analyzed; and the parameters of KP, KI, and KD in the proportional–integral–derivative control method are obtained according to the Ziegler–Nichols controller. The performance of pole climbing based on micro pole-climbing robot prototype was tested. By using this strategy of climbing pole, the self-continuous climbing with controllable stride is realized, and the angular velocity fluctuation of the five-bar mechanism driven by steering gear is reduced. The average time of a single step is 27 s, the maximum relative error of step distance is 4.6%, and the average relative error is 2.8%. These results confirm that the structure scheme and the strategy of climbing pole are feasible.